(untitled) (Third Sector Social Economic Review, 2024)
Economic development refers to increasing the welfare level of countries in economic and social areas by making optimal use of production factors and resources. In the context of state-development relations, three main development approaches can be mentioned. Among these approaches, the traditional developmentalist state approach, advocates that the public sector should be more active in the economy; the neo-liberal development approach advocates reducing the role of the public sector in the market and downsizing the state; and the new developmentalist state approach advocates a balanced reflection of these two views on the market. Today, countries aim to develop by developing socio-economic policies in line with inclusive growth and the new developmental state approach. In this context, the criteria for success are the effective functioning of the market mechanism, positive developments in socio-economic indicators and the achievement of the economic goals. In the context of liberal economic policies, the failure of optimal allocation of resources under market conditions in the context of liberal economic policies leads to market failure, while ineffective public interventions policies lead to government failure. At this point, it is necessary to be aware of economic problems such as unemployment, inflation and negative economic growth caused by these two types of failure while developing the development policies of countries. For this purpose, this study critically examines the economic policies implemented in Turkey since the foundation of the republic within the framework of the concepts of market failure and government failure, the Keynesian interventionist state approach and the Turkish practice of the neo-liberal developmentalist state approach.